Kompres Daun Kubis (Brassica Oleracea Var. Capitata) Sebagai Upaya Mengurangi Nyeri Payudara Pada Ibu Menyusui - Kamila, Nurul Auliya; Suryatim Pratiwi, Yopi (Journal of Fundus, 2025)
Background: Breastfeeding is a natural event for women that is beneficial for both mother and baby. One of the breastfeeding problems that often occurs in the early postpartum period is breast engorgement. Breast engorgement is caused by narrowing of the lactiferous ducts or by glands that are not completely emptied. Breast engorgement occurs due to increased blood flow to the breasts along with breast milk production. Ineffective breastfeeding frequency that can be caused by several factors including sore nipples during breastfeeding, the mother's decision to occasionally delay breastfeeding, and inefficient breastfeeding techniques are some of the causes of breast engorgement. This is painful and swollen, and can occur in part or all of the breasts. The general objective of this study was to determine the effect of giving cabbage leaf compresses on the intensity of pain and breast engorgement in breastfeeding mothers. Method: This research method uses Pre-Experimental with a One group pre test-post test design. The population in this study were all multiparous breastfeeding mothers within 7 days of postpartum with a sample of 19 breastfeeding mothers. Results: This study shows that there is an effect of cabbage leaf compresses on the intensity of pain and breast swelling in breastfeeding mothers with a p value of 0.01 or p <0.05. Conclusion: There is an effect of giving cabbage leaf compresses on the intensity of pain and breast swelling in breastfeeding mothers.